2009
DOI: 10.1016/j.jchromb.2009.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of sulfur-containing compounds involved in the metabolism and transport of cysteamine and cystamine. Regional differences in cerebral metabolism

Abstract: An HPLC method with coulometric detection is presented for the quantitation of cysteamine, cystamine, thialysine, glutathione, glutathione disulfide and an oxidized metabolite of thialysine [S-(2-aminoethyl)-L-cysteine ketimine decarboxylated dimer (AECK-DD)]. The advantage of coulometric detection is that derivatization is unnecessary if the analyte is redox sensitive. The method was used to quantitate several sulfur-containing compounds in plasma and brain following gavage feeding of cysteamine to rats. Cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 61 publications
7
50
1
Order By: Relevance
“…8,25 Recently, Pinto and coworkers reported that the brain of rat seems to have the capacity to synthesize AECK-DD when supplied with cysteamine (250 mg/kg body weight) by gavage treatment. 13 However, they were unable to detect AECK-DD in the brain of adult rats fed a standard rat chow, without cysteamine supplementation. 13 In the present study, we found only trace amounts of AECK-DD in plasma and liver of mice fed the control diet.…”
Section: ■ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,25 Recently, Pinto and coworkers reported that the brain of rat seems to have the capacity to synthesize AECK-DD when supplied with cysteamine (250 mg/kg body weight) by gavage treatment. 13 However, they were unable to detect AECK-DD in the brain of adult rats fed a standard rat chow, without cysteamine supplementation. 13 In the present study, we found only trace amounts of AECK-DD in plasma and liver of mice fed the control diet.…”
Section: ■ Discussionmentioning
confidence: 98%
“…13 However, they were unable to detect AECK-DD in the brain of adult rats fed a standard rat chow, without cysteamine supplementation. 13 In the present study, we found only trace amounts of AECK-DD in plasma and liver of mice fed the control diet. These traces of AECK-DD found in plasma and liver of control mice could come from diet, due to the fact that the control diet contains a very low amount of AECK-DD, likely due to its maize wheat and soya derivatives contents.…”
Section: ■ Discussionmentioning
confidence: 98%
“…It is uncertain whether cysteamine plasma levels reflect cysteamine tissue levels. Studies on animals treated with various doses of cysteamine permitted the assessment of the aminothiol concentration in various tissues, however, the published data differ by several orders of magnitude between groups (from 0.1 to 350 nmol/g of tissue) (Coloso et al 2006, Pinto et al 2009, Pitari et al 2000). Cysteamine levels in mouse liver, kidney and brain of 0.16, 0.35 and 0.11 mol/g of tissue, respectively, were reported after homogenates reduction with dithiothreitol (Coloso et al 2006).…”
Section: Caveatsmentioning
confidence: 99%
“…The alternative CBS reaction using cysteamine may occur in particularly in the brain where very little cysteamine dioxygenase is present and appreciable amounts of CBS are found. Thialysine has been detected in brain tissues following gavage feeding of cysteamine in rats (Pinto et al 2009). In addition, thialysine has been detected in urine of normal human adults, suggesting thialysine may even be a natural occurring metabolite (Yu et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC system consisted of a liquid chromatograph equipped with an eight-channel CoulArray detector (ESA, Inc., Chelmsford, MA) (35,36). Sample aliquots are injected directly onto a Bio-Sil ODS-5S, 5-m particle size, 4.0 ϫ 250 mm, C18 column (Bio-Rad Life Science Research Group) and eluted with a mobile phase consisting of 50 mM NaH 2 PO 4 , 50 M octane sulfonic acid, and 3% (v/v) acetonitrile (pH 2.62) at a flow rate of 1 ml/min.…”
mentioning
confidence: 99%